Analysis of Regional Timelines To Set Up a Global Phase III Clinical Trial in Breast Cancer: The Adjuvant Lapatinib and/or Trastuzumab Treatment Optimization Experience. (28th January 2013) - Metzger‐Filho, Otto; de Azambuja, Evandro; Bradbury, Ian; Saini, Kamal S.; Bines, José; Simon, Sergio D.; Van Dooren, Veerle; Aktan, Gursel; Pritchard, Kathleen I.; Wolff, Antonio C.; Smith, Ian; Jackisch, Christian; et al.
Abstract : Learning Objectives: Discuss methods for improving the efficiency of global clinical trials. Explain the need for national regulatory authorities and collaborative cancer groups to initiate efforts to quicken the activation process in their countries. Describe the activation process of phase III studies and its complex and heterogeneous regulation across different geographic and economic regions. Purpose: This study measured the time taken for setting up the different facets of Adjuvant Lapatinib and/or Trastuzumab Treatment Optimization (ALTTO), an international phase III study being conducted in 44 participating countries. Methods: Time to regulatory authority (RA) approval, time to ethics committee/institutional review board (EC/IRB) approval, time from study approval by EC/IRB to first randomized patient, and time from first to last randomized patient were prospectively collected in the ALTTO study. Analyses were conducted by grouping countries into either geographic regions or economic classes as per the World Bank's criteria. Results: South America had a significantly longer time to RA approval (median: 236 days, range: 21–257 days) than Europe (median: 52 days, range: 0–151 days), North America (median: 26 days, range: 22–30 days), and Asia‐Pacific (median: 62 days, range: 37–75 days). Upper‐middle economies had longer times to RA approval (median: 123 days, range: 21–257 days) than high‐income (median: 47 days, range: 0–112 days) and lower‐middle income economies (median: 57 days, range: 37–62 days). No significant difference was observed for time to EC/IRB approval across the studied regions (median: 59 days, range 0–174 days). Overall, the median time from EC/IRB approval to first recruited patient was 169 days (range: 26–412 days). Conclusion: This study highlights the long time intervals required to activate a global phase III trial. Collaborative research groups, pharmaceutical industry sponsors, and regulatory authorities should analyze the current system and enter into dialogue for optimizing local policies. This would enable faster access of patients to innovative therapies and enhance the efficiency of clinical research. Abstract : This study measured the time taken for setting up the different facets of an international phase III study being conducted in 44 participating countries.